Evaluation of repellents efficacy against Anopheles gambiae s.s.; an anthropophilic malaria vector - Katunzi, Gerald; Munga, Stephen; Nkwengulila, Gamba; Kweka, Eliningaya; Matias, Jonathan R; Godfrey, Gilbert M (Journal of Health & Biological Sciences, 2015)
Reduction of human-vector contact is of epidemiological importance in malaria control. Repellents can be used to complement the existing intervention tools against malaria vectors. Thus, evaluation of efficacy of additional mosquito repellents and /or attractants is of great significance for personal protection tools against malaria vectors. This study evaluated the repellence efficacy of menthol-propylene-glycol-carbonate (MR08) and Lemon grass (LG) against Anopheles gambiae. Experiments were performed in a room which was 7.8 meters by 3.9 meters in dimension. Three experimental set ups were performed, i) comparison of 10 hours worn sock and unworn sock; ii) comparison of 10 hours worn sock treated with MR08 against worn sock alone, and iii) comparison of 10 hours worn sock treated with LG against worn sock alone. CDC miniature light traps were used to evaluate the recovery of released mosquitoes using both repellents and attractants. After initial trials, a concentration of 500 ppm was selected for all repellents. Among 1800 mosquitoes released into the experimental room, 1230 were recovered by CDC light traps while the remaining 570 were found within the experimental room. Among those collected by light traps, 1185 were collected by traps with worn sock alone. A worn sock treated with either MR08 or Lemon grass significantly repelled An.gambiae compared to worn sock alone. The findings of this study demonstrate that MR08 and lemon grass have inhibition efficiency against mosquito stings but further field evaluations are required for observed findings against wild populations of An.gambiae at lower Moshi using slow release method.